Wearable Knee Support Sensor for Real-Time Knee Flexion Monitoring - Ayffa Eriqha Rajali,; Muhammad Rusydi Muhammad Razif,; Nurul Hasyimah Mohd Mustapha,; Ili Najaa Aimi Mohd Nordin,; Muhammad Ammar Hafidz Mohamed Azly, (Progress in Engineering Application and Technology, 2026)
Wearable rehabilitation technologies are increasingly used to support continuous and objective monitoring of joint movement during recovery. This project presents the development of a wearable knee support sensor system for real-time knee flexion monitoring in rehabilitation applications. A flexible resistive sensor fabricated using conductive threads composed of polyester, silver, and stainless-steel fibres embedded within a flexible rubber substrate is integrated into a knee support to detect knee bending through resistance variation. An ESP32-S3 microcontroller acquires the sensor data and transmits the measurements wirelessly to a cloud based ThingsBoard dashboard for real-time visualization and analysis. Experimental results demonstrate a strong and consistent correlation between knee flexion angle and resistance values, confirming stable and repeatable sensor performance. Based on predefined resistance thresholds, the system automatically classifies knee condition into normal movement, moderate stiffness, or conditions requiring physiotherapy attention, which are displayed on the dashboard in real time. The experiment indicate that the developed system provides reliable knee flexion measurement, reduces reliance on manual assessment, and offers a practical solution for both clinical and home-based knee rehabiing.